Physicochemical, vitamin B and sensory properties of rice obtained by system of rice intensification (SRI) - Nur Haqim, I.; Aminah, A.; Anizan, I. (Universiti Kebangsaan Malaysia, 2013)
Organic rice using different cultivation methods namely system of rice intensification (SRI) and local organic rice (BOT) were studied and compared with conventional non organic rice (BBO). One kg of the SRI organic rice was obtained from research plot in Tunjung, Kelantan. Physical and cooking properties were determined using the average weight of 100 kernel, length-breadth ratio (L/B ratio), minimum cooking time, water uptake ratio and percentage of gruel solid loss. Amylose content was determined by iodine-binding method. Thiamine and niacin content were determined by HPLC. Results of the study showed that weight of non organic rice (21.2 mg) was significantly higher (p≤0.05) than SRI organic rice (19.7 mg) or conventional (19.4 mg). Minimum cooking time of SRI organic rice was 19.5 min. The amylose content of conventional rice was the highest (16.6%) followed by SRI organic rice (15.6%) and conventional organic rice (15.3%). Vitamin B1 and B3 contents of organic rice were higher than non-organic rice. The means sensory score of all attributes of SRI cooked rice were the highest. Thus it can be concluded that rice cultivated using SRI resulted in comparatively better physicochemical characteristics and sensory quality compared with other methods.